Enhancing Precision Medicine Predictions via Explainable Artificial Intelligence Models Integrating Genomic Variants and Clinical Phenotypic Profiles - Spencer Lockwood; Wincent Blarke; Ivan Grawford (Bioinformatics Insights and Analytics, 2026)
Precision medicine has emerged as one of the most transformative paradigms in contemporary healthcare, promising individualized diagnostics, treatment strategies, and preventive interventions through the integration of genomic, clinical, behavioral, and environmental data. Despite major advances in artificial intelligence applications for healthcare prediction, substantial limitations remain in the interpretability, fairness, scalability, and clinical trustworthiness of predictive systems that integrate genomic variants with complex phenotypic profiles. Many existing machine learning architectures achieve high predictive performance while simultaneously functioning as opaque computational systems that provide limited explanatory insight into clinical reasoning processes. This lack of transparency poses serious challenges for regulatory oversight, physician adoption, ethical accountability, and patient trust, particularly in high-stakes medical contexts involving cancer therapeutics, cardiovascular disease risk stratification, and rare disease diagnosis. This paper examines the evolving role of explainable artificial intelligence in enhancing precision medicine predictions through integrated genomic-phenotypic modeling frameworks. The study develops a systems-oriented analysis of explainability infrastructures, multimodal learning architectures, federated biomedical data ecosystems, and governance mechanisms that support interpretable predictive medicine at scale. Particular attention is devoted to structural trade-offs between model accuracy and interpretability, the operational challenges of integrating heterogeneous biomedical data, and the policy implications associated with fairness, bias mitigation, and data sovereignty. The paper further explores emerging deployment architectures involving graph neural systems, transformer-based biomedical language models, causal inference frameworks, and hybrid symbolic-neural approaches designed to improve transparency and clinical accountability. Through interdisciplinary analysis spanning computational biology, clinical informatics, healthcare governance, and AI systems engineering, this research proposes a comprehensive conceptual framework for sustainable, explainable, and clinically deployable precision medicine infrastructures capable of supporting next-generation healthcare ecosystems.